Xylanolytic Extremozymes Retrieved From Environmental Metagenomes: Characteristics, Genetic Engineering, and Applications - Verma, Digvijay; Satyanarayana, Tulasi (Frontiers in Microbiology, 2020)
Xylanolytic enzymes have extensive applications in paper, food and feed, pharmaceutical, and biofuel industries. These industries demand xylanases that are functional under extreme conditions like high temperature, acidic/alkaline pH, and others, which are prevailing in bioprocessing industries. Despite the availability of several xylan-hydrolyzing enzymes from cultured microbes, there is a huge gap between what is available and that industries require. DNA manipulations as well as protein engineering techniques are also not quite satisfactory in generating xylan-hydrolyzing extremozymes. With the compound annual growth rate (CAGR) of 6.6% of xylan hydrolyzing enzymes in the global market, there is a need for xylanolytic extremozymes. Therefore, metagenomic approaches have been employed to uncover the hidden xylanolytic genes that were earlier inaccessible in culture-dependent approaches. An appreciable success has been achieved in retrieving several unusual xylanolytic enzymes with novel and desirable characteristics from different extreme environments using functional and sequence-based approaches of metagenomics. Moreover, the Carbohydrate Active enZYmes (CAZy) database includes approximately four hundred GH-10 and GH-11 unclassified xylanases. This review discusses sources, characteristics, and applications of xylanolytic enzymes obtained through metagenomic approaches and their amelioration by genetic engineering techniques.